Performance in the Post-Pandemic Era: A Study on Non-Face-to-Face Service Innovations in Local Government Institutions - Perdanaputra, Decky; Fahmi, Ade; Sa’adih, Sa’adih (JURNAL SOSIAL DAN HUMANIS SAINS, 2023)
This study examines the performance of non-face-to-face public service innovations implemented by local government institutions in the post-pandemic era. Using a qualitative descriptive approach, data were collected through semi-structured interviews with public officials and document analysis from selected municipal governments. The findings reveal that while digital service innovations have improved accessibility, efficiency, and continuity of service delivery, they also face challenges such as digital inequality, limited infrastructure, staff capacity gaps, and the absence of unified regulatory frameworks. Moreover, public trust in digital services is influenced by data privacy, responsiveness, and user experience. The study underscores that technological tools alone are insufficient; effective implementation requires institutional readiness, digital literacy, ethical governance, and citizen engagement. As public expectations shift toward digital convenience and transparency, local governments must adopt inclusive, adaptive, and sustainable strategies to ensure long-term performance improvement in public service delivery. This research contributes to the discourse on post-pandemic governance by highlighting the need for an integrated approach to digital public service innovation.